A comprehensive examination and analysis of the effectiveness and safety of finerenone for the treatment of diabetic kidney disease: a systematic review and meta-analysis - Chen, Jianyu; Xue, Jisu; Chen, Jiahui; Xie, Tingfei; Sui, Xiaolu; Zhang, Yanzi; Zhang, Aisha; Xu, Yunpeng; Chen, Jihong (Frontiers in Endocrinology, 2024)
ObjectivesThe study will evaluate the effectiveness and safety of finerenone in patients diagnosed with diabetic kidney disease (DKD).MethodsVarious databases including PubMed, Sinomed, Web of Science, Embase, Clinical Trials, and Cochrane Library were systematically reviewed for pertinent studies published from the beginning to February 2024.This meta-analysis utilized RevMan 5.3 and Stata 15.1.ResultsThe analysis of 4 randomized controlled trials involving 13,943 participants found that finerenone treatment significantly decreased the urine albumin-to-creatinine ratio compared to placebo. Additionally, the risk of COVID-19, cardiovascular events, and estimated glomerular filtration rate(eGFR) reduction of at least 40% were all significantly lower in the finerenone treatment group. However, the finerenone group did experience higher baseline increases in serum potassium levels. The meta-analysis revealed that there was no variation in the likelihood of general negative outcomes (RR 1.00, 95% CI 0.98, 1.01, I2 = 0%) and the occurrence of cancers (RR 0.99, 95% CI 0.83, 1.18,I2 = 0%) among the two categories.ConclusionOur study demonstrates that finerenone has the potential to lower the chances of end-stage kidney disease, renal failure and cardiovascular mortality in individuals with diabetic kidney disease. It is important to monitor for hyperkalemia risk. The administration of finelidone among individuals with diabetic kidney disease may potentially mitigate the susceptibility to contracting COVID-19.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024536612.